Analysis of User Experience of the CapCut Application in Generation Z for Social Media Content Using the User Experience Questionnaire Method - Wulan, Damar; Syaifullah; Saputra, Eki; Rahmawita, Medyantiwi; Marsal, Arif (Universitas Negeri Semarang, 2024)
Purpose: In the midst of these dynamics of change, research, development and application of technology continues to be the main focus in efforts to achieve progress and efficiency in various sectors of life. Generation Z has been the primary architect of cultural and behavioral change on social media. One of the most prominent characteristics of Generation Z is their desire to create